COVID-19 vaccine hesitancy: Vaccination intention and attitudes of community health volunteers in Kenya. - Joachim Osur; Evelyne Muinga; Jane Carter; Shiphrah Kuria; Salim Hussein; Edward Mugambi Ireri (Public Library of Science (PLoS), 2022)
In Kenya, community health volunteers link the formal healthcare system to urban and rural communities and advocate for and deliver healthcare interventions to community members. Therefore, understanding their views towards COVID-19 vaccination is critical to the country's successful rollout of mass vaccination. The study aimed to determine vaccination intention and attitudes of community health volunteers and their potential effects on national COVID-19 vaccination rollout in Kenya. This cross-sectional study involved community health volunteers in four counties: Mombasa, Nairobi, Kajiado, and Trans-Nzoia, representing two urban and two rural counties, respectively. COVID-19 vaccination intention among community health volunteers was 81% (95% CI: 0.76-0.85). On individual binary logistic regression level, contextual influence: trust in vaccine manufacturers (adjOR = 2.25, 95% CI: 1.06-4.59; p = 0.030); individual and group influences: trust in the MoH (adjOR = 2.12, 90% CI: 0.92-4.78; p = 0.073); belief in COVID-19 vaccine safety (adjOR = 3.20, 99% CI: 1.56-6.49; p = 0.002), and vaccine safety and issues: risk management by the government (adjOR = 2.46, 99% CI: 1.32-4.56; p = 0.005) and vaccine concerns (adjOR = 0.81, 90% CI: 0.64-1.01; p = 0.064), were significantly associated with vaccination intention. Overall, belief in COVID-19 vaccine safety (adjOR = 2.04, 90% CI: 0.92-4.47 p = 0.076) and risk management by the government (adjOR = 1.86, 90% CI: 0.94-3.65; p = 0.072) were significantly associated with vaccination intention. Overall vaccine hesitancy among community health volunteers in four counties in Kenya was 19% (95% CI: 0.15-0.24), ranging from 10.2-44.6% across the counties. These pockets of higher hesitancy are likely to negatively impact national vaccine rollout and future COVID-19 vaccination campaigns. The determinants of hesitancy arise from contextual, individual and group, and vaccine or vaccination specific concerns, and vary from county to county.